The effect of Deffered Tax Assets, Tax Expense and Current Tax on Earnings Management : The effect of Deffered Tax Assets, Tax Expense and Current Tax on Earnings Management - Sari, Dewi Puspita; Afandi, Agus (Jurnal Penelitian Ekonomi Dan Akuntansi, 2023)
Research to analyze and test deferred tax assets, deferred tax expenses and current tax expenses on earnings management. This type of research is quantitative with an associative approach and secondary data sources in the form of annual reports. The population in the consumer goods sector manufacturing companies listed on the IDX during 2016-2021 was 81 companies. Obtained a sample based on purposive sampling technique of 9 companies for 6 periods or 54 observation data. To use the Eviews series 9 program with the panel data regression analysis method. The results of this study indicate that deferred tax assets, deferred tax expenses, and current tax expenses together have an effect on earnings management. deferred tax assets have no effect on earnings management, deferred tax expenses have a negative and significant effect, and current tax expenses have a positive and significant effect on earnings management.